2022
DOI: 10.21037/atm-21-2494
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal multiorgan procurement from slaughterhouse pigs: a bespoke model in organ donation after circulatory death for ex vivo organ perfusion compliant with the 3 Rs (Reduction, Replacement & Refinement)

Abstract: Background: Advances in organ preservation, reconditioning and assessment have been driven by the increasing necessity to utilise organs from extended criteria donors, particularly donors after circulatory death. Research efforts in this area have aided translation of machine perfusion technology into clinical practice. Pigs are anatomically and physiologically similar to humans and are an excellent model. However, conducting large animal experimental research is challenging and typically limited by ethical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…We acknowledge that the use of a slaughterhouse model presents more variability in comparison to an animal house model, where the environment is more controlled. However, we have refined this method of retrieval over a number of years and previously described the strengths and limitations ( 50 ). We have shown acceptable reproducibility in preclinical dose–response studies where kidneys underwent normothermic perfusion as a basis for a clinical trial ( 17 ) and have also demonstrated that this method of multiple organ procurement is adequate for comparing different preservation methods in pig pancreases ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that the use of a slaughterhouse model presents more variability in comparison to an animal house model, where the environment is more controlled. However, we have refined this method of retrieval over a number of years and previously described the strengths and limitations ( 50 ). We have shown acceptable reproducibility in preclinical dose–response studies where kidneys underwent normothermic perfusion as a basis for a clinical trial ( 17 ) and have also demonstrated that this method of multiple organ procurement is adequate for comparing different preservation methods in pig pancreases ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…This method is advantageous because it reduces cold ischemia times, provides an opportunity for quality assessment, and decreases organ degradation (Tembo and Nonga, 2015). The development of ex vivo organ perfusion systems has been extensively researched using multiorgan procurement techniques, which can maintain organ viability comparable to levels observed in organs donated from circulatory death models (Dengu et al, 2022). Slaughterhouse porcine organs, in particular, have been used in several ex vivo perfusion investigations.…”
Section: Preserving Harvested Organsmentioning
confidence: 99%
“…Ex vivo perfusion of porcine organs has proved to be a valuable tool in translational research due to the remarkable similarities between human and porcine anatomy and physiology. These porcine organ perfusion models have been employed for the study of organ transplantation and the development of ex vivo perfusion technology but have also been used widely to study invasive diseases [ 1 ]. Wanford et al used ex vivo perfusion models of porcine liver and spleen to demonstrate intracellular replication of Klebsiella pneumoniae in tissue macrophages, highlighting the pathophysiology of hepatic abscess formation and the importance of optimising antimicrobial treatment strategies [ 2 ].…”
Section: Introductionmentioning
confidence: 99%